Improvement of productivity in aluminum extrusion process with experimental aluminum alloy 6063 cast billets - Navas-Olmedo, Bladimiro Hernán (2017)
The chemical composition of the raw material has a direct effect on the extrusion process and it is reflected in the key performance indicators. By varying main alloying elements levels to produce AA 6063 cast billets made in horizontal continuous casting machine, it was possible to increase productivity levels during extrusion process. During nine consecutive work shifts using homogenized billets of aluminum alloy 6063, a 7.37 mm/s average extrusion speed was registered; it means there was a significant increase in productivity of 13.54 % with an average recovery of 82.42 %.